A New Approach to Social Engineering with Natural Language Processing: RAKE - Aydogan, Ahmet Furkan; An, Min Kyung; Yilmaz, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2021)
Nowadays, with the advancement of technology, the way of thinking of communities has become easily manipulated. Scientific results put forward during the Arab Spring period, which is one of the biggest examples, show that social media is easily used to guide people in different ways. This paper introduces our project, Rake, which has emerged as a method against the aforementioned manipulations. The Rake used Nat-ural Language Processing and Machine Learning algorithms, to generate its own dataset and it consist of three major procedures: Emotion, Reaction, and Word Mapping, Rake is a high performance application that can adapt to areas such as community analysis, business area analysis and advertising. As shown in the experiments, it has achieved a machine learning performance of 94%. In addition, the stages that convey how to adopt the Rake application in large-scale projects were included in the study. © 2021 IEEE.
9th International Symposium on Digital Forensics and Security, ISDFS 2021 -- 28 June 2021 through 29 June 2021 -- Elazig -- 171186
Keywords: Machine Learning; Manipulation Techniques; Natural Language Processing; Social Engineering